BIMBINGAN TEKNIS DEKAPSULASI DAN KULTUR ARTEMIA DI SMK IBRAHIMY 1 SUKOREJO - Dimas Galang Prakosa; Abdul Muqsith; Abdul Wafi; Musyaffa Rafiqie; Ach. Khumaidi (LP2M Universitas Ibrahimy, 2022)
Natural feed has a very important role in supporting the success of aquaculture. The availability of natural feed is a key factor in the seed / fry phase, where at that phase the fish are still unable to consume additional feed, namely pellet feed. The objectives of this activity are: (1) Introducing Artemia, Improving the entrepreneurial spirit and entrepreneurial motivation, (3) Increasing the knowledge and abilities of SMK Ibrahimy 1 Sukorejo students in terms of decapsulation and artemia culture. This activity targets the fishery students of SMK Ibrahimy 1 Sukorejo, Department of Agribusiness, Brackishwater and Marine Fisheries. Service activities are carried out using lecture and demonstration/practice methods. Evaluation was carried out on the ability of participants to practice artemia decapsulation and artemia culture, indicators of the success of this practice are theoretical and practical knowledge of Artemia sp culture. The success of this activity can be seen from the very high enthusiasm of students and the increasing knowledge of students about the decapsulation of Artemia sp. The obstacle that is used as an evaluation in this activity is that several additional tools are still needed to maximize the decapsulation practice of Artemia sp.